2004
DOI: 10.1080/15389580490269047
|View full text |Cite
|
Sign up to set email alerts
|

Living Dangerously: Driver Distraction at High Speed

Abstract: Recent research indicates that cell phone use can distract drivers from safe vehicle operation. However, estimates of the prevalence of cell phone use while driving have been limited to daytime hours and low-speed roadways. This paper describes the results of a study to estimate rates of cell phone use and other distractions by examining approximately 40,000 high-quality digital photographs of vehicles and drivers on the New Jersey Turnpike. The photographs, which originally were collected as part of a separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
32
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 5 publications
10
32
4
Order By: Relevance
“…13,14,24 Parents in our study reported more drowsy driving compared with results from a national survey of adult drivers. 33 How the combinations of distractions and unsafe driving behaviors interact to influence the driving performance specifically among drivers of child passengers is not well understood.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…13,14,24 Parents in our study reported more drowsy driving compared with results from a national survey of adult drivers. 33 How the combinations of distractions and unsafe driving behaviors interact to influence the driving performance specifically among drivers of child passengers is not well understood.…”
Section: Discussionsupporting
confidence: 44%
“…The study team developed survey questions to assess child passenger safety practices based on published literature 1,20,24 and pilot tested the instrument with 21 parents. Modifications were made to clarify confusing questions identified in pilot testing.…”
Section: Methodsmentioning
confidence: 99%
“…There is abundant evidence that the use of mobile telephones in vehicles causes distraction 4 and increases the risk of crashes. 5 Technologies that allow for hands-free, voice-activated communication produce less distraction, but inevitably divert some attention away from the task at hand.…”
Section: Creating Dangermentioning
confidence: 99%
“…For these video clips secondary task type was rated and driving parameters with secondary tasks were compared to driving without a secondary task. Johnson et al (2004) analyzed 40,000 photographs taken in July 2001 at the New Jersey Turnpike and rated secondary task occupation of the randomly photographed drivers. Klauer et al (2006) finally reported the part of the 100 car naturalistic driving study concerning driver distraction and inattention and its relation to crashes, near crashes and incidents.…”
Section: Data Sourcementioning
confidence: 99%